Development of Broadband Low Actuation Voltage RF MEM Switches - S. C. Shen; D. Becher; Z. Fan; D. Caruth; Milton Feng (Active and Passive Electronic Components)
Low insertion loss, high isolation RF MEM switches have been thought of as one of the most attractive devices for space-based reconfigurable antenna and integrated circuit applications. Many RF MEMS switch topologies have been reported and they all show superior RF characteristics compared to semiconductor-based counterparts. At the University of Illinois, we developed state-of-the-art broadband low-voltage RF MEM switches using cantilever and hinged topologies. We demonstrated promising sub-10 volts operation for both switch topologies.The switches have an insertion loss of less than 0:1 dB, and an isolation of better than 25 dB over the frequency range from 0.25 to 40 GHz. The RF Model of the MEM switch was also established. The low voltage RF MEM switches will provide a solution for low voltage and highly linear switching methods for the next generation of broadband RF, microwave, and millimeter-wave circuits.